Ma’rifatullah of Ibn ‘Ata’illah in the Face of ‘The Peak Experience’ of Abraham Maslow - Ihsan, Nur Hadi; Mudin, Moh. Isom; Abdul Rohman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
When a person achieves their life’s principal goal, they feel happier. They experience a diverse psychological condition compared to the average individual, reaching the culmination of their experience at that point. Within the Islamic heritage, particularly in Sufism, the pinnacle aim is ma‘rifatullah. The Sufi Ibn ‘Ata’illah has extensively discussed the idea of ma‘rifatullah. Meanwhile, Abraham Maslow’s concept of the peak experience has gained widespread acceptance in Western psychology. This paper explores the similarities and differences between these two concepts, comparing ma‘rifatullah with the peak experience. Data for this paper was collected using documentary techniques. The authors employ a descriptive, content-analytic comparative method to analyze these issues. This research is conducted within the discipline of psychology, utilizing a Sufi approach. The study concludes that there are both parallels and contrasts between these concepts. The similarity lies in the ecstatic condition experienced by the individual. However, the discrepancies are substantial, primarily due to the differences in the underlying worldviews. Ma‘rifatullah is based on a revelation-based Islamic worldview, while the peak experience is grounded in a Western worldview based on secular humanism.